2023
DOI: 10.1101/2023.02.22.23286294
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessing the feasibility of Phase 3 vaccine trials against Marburg Virus Disease: a modelling study

Abstract: Background: Outbreaks of Marburg virus disease (MVD) are rare and small in size, with only 16 recorded outbreaks since 1967, only two of which involved more than 100 cases. It has been proposed, therefore, that Phase 3 trials for MVD vaccines should be held open over multiple outbreaks until sufficient end points accrue to enable vaccine efficacy (VE) to be calculated. Here we estimate how many outbreaks might be needed for VE to be estimated. Methods: We adapt a mathematical model of MVD transmission to simul… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Most outbreaks are relatively small and need to be controlled quickly using existing infection control and public health measures. Therefore, it is suggested that multiple outbreaks could be used to conduct Phase 3 trials for MVD vaccines until sufficient endpoints have been accumulated to assess vaccine efficacy (VE) and can be estimated by estimating the number of outbreaks required [ 77 ].…”
Section: Reviewmentioning
confidence: 99%
“…Most outbreaks are relatively small and need to be controlled quickly using existing infection control and public health measures. Therefore, it is suggested that multiple outbreaks could be used to conduct Phase 3 trials for MVD vaccines until sufficient endpoints have been accumulated to assess vaccine efficacy (VE) and can be estimated by estimating the number of outbreaks required [ 77 ].…”
Section: Reviewmentioning
confidence: 99%